CRISPR: express delivery to any DNA address. (17th May 2016) - Peterson, A
Abstract : The sudden emergence and worldwide adoption of CRISPR gene‐editing technology confronts humanity with unprecedented opportunities and choices. CRISPR's transformative impact on our future understanding of biology, along with its potential to unleash control over the most fundamental of biological processes, is predictable by already achieved applications. Although its origin, composition, and function were revealed only recently, close to 3000 CRISPR‐based publications have appeared including insightful and diversely focused reviews referenced here. Adding further to scientific and public awareness, a recent symposium addressed the ethical implications of interfacing CRISPR technology and human biology. However, the magnitude of CRISPR's rapidly emerging power mandates its broadest assessment. Only with the participation of a diverse and informed community can the most effective and humanity‐positive CRISPR applications be defined. This brief review is aimed at those with little previous exposure to the CRISPR revolution. The molecules that constitute CRISPR's core components and their functional organization are described along with how the mechanism has been harnessed to edit genome structure and modulate gene function. Additionally, a glimpse into CRISPR's potential to unleash genetic changes with far‐reaching consequences is presented.